(untitled) (Scientific journal of the Fergana State University, 2026)
In this paper, the sorption isotherm of Cr(VI) ions from artificial solutions on the industrially used anionite AN-31 was investigated. The Langmuir and Freundlich isotherm models were used to estimate the sorption isotherm. The results show that the adsorption isotherm follows the Freundlich isotherm model.